1997
DOI: 10.1016/s1078-5884(97)80064-0
|View full text |Cite
|
Sign up to set email alerts
|

Vein quality influences neointimal hyperplasia in an organ culture model of human saphenous vein

Abstract: Pre-existing vein quality as measured by PIT correlates with the development of neointimal hyperplasia in culture, adding further support to clinical evidence that poor vein quality predisposes to vein graft stenosis due to an inherent susceptibility to intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…As published previously, 31 a high proportion of saphenous veins used for coronary artery bypass grafting have a preexisting thickening. VSMCs in these thickenings are longitudinally orientated, in contrast to the circumferentially orientated medial VSMCs.…”
Section: Resultsmentioning
confidence: 58%
“…As published previously, 31 a high proportion of saphenous veins used for coronary artery bypass grafting have a preexisting thickening. VSMCs in these thickenings are longitudinally orientated, in contrast to the circumferentially orientated medial VSMCs.…”
Section: Resultsmentioning
confidence: 58%
“…However, most of the experiments dealing with assessment of IH development were performed using either cultured endothelial cell lines or nonperfused ex vivo venous segments [9,13,[15][16][17][22][23][24]. Since low sheer stress may be one of the major stimuli leading to IH development [10,25], ex vivo perfusion is advantageous in order to test modulations of hemodynamics, anastomosis configuration and graft design with respect to IH development under standardized conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Davies et al [123] and Wilson et al [124] have shown diffuse changes in intimal hyperplasia and muscular hypertrophy in saphenous and cephalic veins prior to their use in bypass surgery, suggesting that pre-existing disease may predispose vein grafts to stenosis due to inherent susceptibility of diseased veins to intimal hyperplasia.…”
Section: Alterations In Gene Expression With Stretch: Similarities Wimentioning
confidence: 99%